The dental health of factory workers in Pasir Gudang, Johor (Malaysia) - Majid, Z. Abdul; Zain, R.B. (1988)
A study on the oral health status of 198 factory workers (in Antara Steel, Pasir Gudang, Johor) was carried out in November 1986. The subjects were predominantly male (94%) and Malay (91%) with an average age of 27.4 years. The prevalence of caries was 87.4% with a mean DMFT of 7.1 ? 5.4. There were 3 subjects with full upper, lower dentures and 16 subjects with partial dentures. Two subjects examined needed dentures but were not wearing them. Thirty five (17.7%) of those examined needed urgent extractions, and 8 needed emergency treatment for fillings. Enamel opacities were found in 141 subjects (75.6%) but only 9 were aware of these defects. Dental health was very poor with 72% examined needing scaling. Seventeen (9%) had gross supra and subgingival calculus. There was a total of 107 (54%) smokers and heavy nicotine stains were found in 41 (20.7%), of the population examined. Examination of soft tissues showed 111 (56%) subjects with recurrent aphthous ulcers whilst 15 (7.6%) suffered from herpes labialis. Five subjects (2.5%) suffered from denture stomatitis whilst the prevalence of other soft tissue lesions was very low.